E-Consulting Dalam Penanganan Kesehatan Kucing Ras (Klinik Kucing) Dengan Metode Forward Chaining - Andrew Kurniawan Vadreas; Dwi Welly Sukma Nirad (Prosiding SISFOTEK, 2018)
Diagnosing disease in cats with the support of expert systems is one of the implementation of technological developments that can solve a problem like a human. The study was conducted at veterinarians and veterinary clinics in the city of Padang. The basic problem in this research is e-consulting in handling cat health which will be made a (Cat Clinic) where to consult various ways to prevent and cure cat diseases early and easy by using forward chaining expert system. This expert system has the ability to diagnose diseases in cats and how to overcome them. Currently how to diagnose disease in cats still manually, by conducting laboratory tests, and using paper as a form of calculation of the results of diagnoses performed by veterinarians. Therefore it is necessary to have expert system more effective and efficient for cat lovers, especially women. This expert system is able to help cat lovers to diagnose diseases in their beloved cat, prevention, and how to cope with them.